Comparison of Morbidity of Three Flank Approaches for Open Renal Surgery (Medical Forum Monthly, 2024)
Objective: The aim of this study was to compare the morbidity of three flank incisions, subcostal, transcostal and supracostal for open renal surgery in terms of incision times, postoperative pain, postoperative hospital stay and long term complications.Study Design: Prospective comparative and analytic study.Place and Duration of Study: This study was conducted at Department of Urology, Nishtar Hospital Multan and Department of Urology, Ghulam Mohamed Maher Medical College/Teaching Hospital Sukkur from January 2007 to December 2011.Materials and Methods: In this study twelve hundred sixty (n-1260) patients who underwent open surgical procedures over a period of five years are analyzed. Patients were studied in three groups. Group A, subcostal, (n-407) 32.3%. Group B transcostal (n-526) 41.7% and Group C, supracostal, included (n-327) 25.9%. Mean incision time in Groups A, B and C was 17.3 min, 21.08 min and 23.81 min respectively. Mean amount of injectable analgesic required in first three post operative days in Groups-A, B and C was 41.36 mg, 46.87 mg and 49.40 mg of Nalbin respectively. Mean Post operative hospital stay in Group A Band C was 4.63, 5 days and 4.64 days respectively.Results: Pleural injury was none in Group A, thirty five (n- 35) cases (6.61%) in Group B and thirty nine (n-39) cases (11.9%) in Group C. Incisional hernia was noted in Group A 12 cases 3%, Group B 6 cases 1.1 % and none in group C.Conclusion: With subcostal approach, incision time, dose of analgesia and pleural injury is minimum but high incidence of incisional hernia is there. In transcostal and supracostal approach the incision time, dose of analgesia and incisional hernia is minimum but incidence of pleural injury is relatively high.